Distribution of hospitals through Baghdad province using Geographic Information System - Najim, Zahraa (Al-Adab Journal, 2021)
This research study the distribution of hospitals in the province of Baghdad Using geographic information system to focus on the shortage of hospitals in specific regions in comparison with other regions. In the distribution of hospitals in the city of Baghdad using Arc GIS program, we noticed that there is a shortage in the number of hospitals in the city of Kadhimiya, Sadr city and other areas compared to the increase in the population in these areas. There are enough hospitals in the area of Andalus square.